2020
DOI: 10.1016/j.petrol.2020.107392
|View full text |Cite
|
Sign up to set email alerts
|

The effect of rock type on natural water flooding and residual oil saturation below free water level and oil water contact: A case study from the Middle East

Abstract: The presence of residual oil below the present day free water level (FWL) and oil water contact (OWC) is common in many fields of the Middle East. This residual oil is seen in reservoirs prior to the start of production.A rock typing study was carried out to investigate the effect of rock types on the presence and distribution of residual oil below the free water level (FWL) and oil water contact (OWC) and potential recovery from ROZ's following water flooding.The rock typing study was carried out by integrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…The results of coring well data show that the common sedimentary structures in the study area mainly include deformation structure, bedding plane structure, bedding structure and biogenic structure (Fig. 5 ) 22 .
Figure 5 Analysis of Sedimentary characteristics of coring Wells.
…”
Section: Methodsmentioning
confidence: 97%
“…The results of coring well data show that the common sedimentary structures in the study area mainly include deformation structure, bedding plane structure, bedding structure and biogenic structure (Fig. 5 ) 22 .
Figure 5 Analysis of Sedimentary characteristics of coring Wells.
…”
Section: Methodsmentioning
confidence: 97%
“…Akai et al [12] used direct numerical simulation to study the mechanism of microscopic displacement during enhanced oil recovery in mixed-wet rocks. Heydari-Farsani et al [13][14][15][16] proposed that the characteristics of reservoirs and structures can affect the location and migration direction of hydrocarbons. Liu et al [17] analyzed the mechanism and effect of nitrogen foam flooding using sand-packing pipe experiments to enhance oil recovery and concluded that high-porosity, highpermeability, and strong edge-water reservoirs entered the high water-cut stage in the middle and late development stages, with the remaining oil mainly distributed at the top and edge of the structure and reservoirs.…”
Section: Nomenclaturementioning
confidence: 99%
“…The trajectory, thermodynamic properties, radial distribution function (RDF), time-related physical quantities, and free energy can be calculated accurately in the process of simulation [6]. The dispersion effect of modified SiO 2 nanoparticles was investigated to improve the practical production owing to the agglomeration of unmodified nanoparticles [7,8].…”
Section: Introductionmentioning
confidence: 99%